2018
DOI: 10.1080/1540496x.2018.1527686
|View full text |Cite
|
Sign up to set email alerts
|

Tax Revenue Trends in Latin America and Asia: A Comparative Analysis

Abstract: Joshua Aizenman and Yothin Jinjarak acknowledge funding from the Asian Development Bank (ADB). The views herein are entirely those of the authors. They do not necessarily represent the views of the ADB, or the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Between 2008 and 2012 period, tax revenue was two percentage points higher than the 1998-2002 period (14.8% instead of 12.6%). It was about one percentage point higher than the 1993-1997 period (13.7%) (Aizenman et al, 2015).…”
Section: Notesmentioning
confidence: 64%
See 1 more Smart Citation
“…Between 2008 and 2012 period, tax revenue was two percentage points higher than the 1998-2002 period (14.8% instead of 12.6%). It was about one percentage point higher than the 1993-1997 period (13.7%) (Aizenman et al, 2015).…”
Section: Notesmentioning
confidence: 64%
“…In addition, the integration of countries into the global economy is often accompanied by a reduction of trade barriers, hence a reduction of trade-based tariffs (Aizenman et al, 2015).…”
Section: Low-income Partner Countries Rely Heavily On Indirect Taxesmentioning
confidence: 99%
“…The power of tax administrations, the levels of corruption and tax morale (or willingness of people to pay taxes) are also strongly linked to the level of tax revenues (OECD, 2014). Aizenman et al (2015) found that in Asia, government effectiveness and institution quality are positively correlated with the level of tax-to-GDP ratio. Geographic location is also relevant: landlocked countries are less able to impose taxes on goods and services entering the country than island countries (UNESCAP, 2014).…”
Section: Factors Influencing Tax-to-gdp Ratiosmentioning
confidence: 99%
“…Namun pendapatan PPN rata-rata terhadap PDB naik sebesar 2% poin PDB di Amerika Latin, sementara itu turun sekitar 1% di Asia. Kesenjangan yang mencolok dalam pemungutan PPN de facto ini mungkin dapat dijelaskan oleh tren yang berbeda dalam variasi tarif PPN aktual di berbagai sektor ekonomi dan penegakan PPN (Aizenman et al, 2019)…”
Section: Pajak Pertambahan Nilai (Ppn)unclassified